(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2018)
Computational Fluid Dynamics (CFD) of indoor environment as well as qualityconsiderations are important element in the study of energy consumption, thermal comfortand indoor air quality in buildings. This paper investigate a comparison work betweenimpinging jet, displacement, and mixing ventilation systems for an isothermal and nonisothermalventilated room for Indoor Air Quality (IAQ) and thermal human comfort underIraqi climate. For IJV system, draught discomfort is the issue of most concern since itsupplies cooled air directly to the occupied zone. This study investigated a number of factorsinfluencing draught discomfort and temperature stratification in an office environment. Theconsidered factors, supply airflow rate and supply air temperature. RNG K-? turbulencemodel was used with the turbulent flow. The second aspect included numerical analyses byadopting ANSYS FLUENT15 code to generate simulation models. A square shaped airsupply device was used with [0.1 times room height (h)] outlet terminal height from the footlevel end. The IJV system proved more efficient than displacement and mixing ventilationsystems. The Air Distribution Performance Index (ADPI) obtained for an isothermal andnon-isothermal ventilated room adopting IJV system gave best values (0.80, 0.83)respectively compared with the other two ventilation systems.